Business process management and supply chain collaboration: effects on performance and competitiveness. Issue 2 (13th March 2017) - Pradabwong, Jiraporn; Braziotis, Christos; Tannock, James D.T.; Pawar, Kulwant S.
Abstract : Purpose: This study aims to examine the interrelationships among business process management (BPM), supply chain collaboration (SCC), collaborative advantage and organisational performance. Design/methodology/approach: Data were collected from 204 manufacturing firms in Thailand, and the interrelationships proposed in the framework were tested via structural equation modelling. Findings: This study highlights the role of intra- and inter-organisational practices and clearly demonstrates the joint role and impact of BPM and SCC, respectively. The results provide empirical evidence that BPM improves both organisational performance and collaborative activities. Also, SCC and collaborative advantage can have indirect positive impacts on organisational performance. Research limitations/implications: This work could be expanded by adopting a supplementary dyadic or extended supply chain (SC) approach and could also consider contextual factors, which were outside of the scope of this study. Practical implications: The BPM approach has a positive impact on organisational performance, which is essential for collaborative activities between a firm and its SC partners. Further, effective BPM and SCC practices lead to enhanced performance and collaborative benefits. Practitioners should be better able to define and measure specific actions relating to their BPM and SCC practices. Originality value: This paper stresses the need to consider the interrelationships between BPM, SCC, collaborative advantage and organisational performance for both direct and indirect effects. Rather than focusing only on improvement at individual firm level, SCC is vital to compete in the market. Improving the effectiveness of SC allows higher organisational performance levels than those that could be achieved in isolation.